Virus-bacteria diagnostic test (vbd-test) in identifying biology teacher’s misconception - Zulfia, Firda Ama; Susilo, Herawati; Listyorini, Dwi (Universitas Negeri Jakarta, 2019)
Virus-Bacteria Diagnostic Test (VBD-Test) is three-tier diagnostic instrument for identification virus and bacteria topics. The purpose of this study was to determine the empirical validity of the VBD-Test and identify misconceptions of virus and bacteria topics in biology teachers in Malang using VBD-Test. The development research model used was the Treagust development model, namely (1) Defining content, (2) Obtaining information, and (3) Developing a diagnostic test. The empirical validity on the VBD-Test was carried out with the Pearson correlation test using Excel, while the reliability on the VBD-Test was carried out with a spearman brown split-half method using Anatest 4.0.2. There are six valid questions and eight invalid questions on the virus topic, while in bacteria topics, there are nine valid questions and six invalid questions. The results of the identification of the teacher’s concept of the virus topic were 33.33% understood the idea, 13.66% false positive, 35.53% false negative, 17.01% did not understand the concept, and 4.39% guessed. While the results of the identification of the teacher’s concept of bacteria topic were 30.13% understood the concept, 9.07% false positive, 227.63% false negative, 23.05% did not understand the concept, and 10.09% guessed. Based on these results, if identification misconception is not made to the teacher, then the misconception will not be known by the teacher on any material, and the learning material submitted by the teacher will remain a misconception so that students will have misconception.